The Role of Family Dynamics and Transgenerational Processes in the Development and Maintenance of Addictive Behaviors: Implications for Systemic Psychotherapeutic Intervention - Sava, Nicu-Ionel; Popa, Aura-Brigitte; Dolea, Mihaela-Cătălina (New Trends in Psychology, 2026)
Addictive behaviors have long been conceptualized as individual disorders primarily grounded in neurobiological vulnerability or maladaptive personality traits. Increasingly, however, systemic perspectives emphasize the relational and developmental contexts in which addiction emerges and is maintained. This article proposes an integrative systemic framework that conceptualizes addictive behavior as a relationally embedded and transgenerational phenomenon, shaped by family dynamics and intergenerational patterns. Drawing on systemic family therapy models—including Bowenian, contextual, structural, and narrative approaches—the paper explores how processes such as triangulation, emotional cutoff, rigid family roles, and transgenerational loyalties may contribute to the persistence of addiction. At the same time, family resources and resilience are examined as central elements in recovery and therapeutic change. The article discusses clinical implications for systemic assessment and intervention, highlighting the importance of multigenerational perspectives, relational safety, and ethical sensitivity in promoting sustainable recovery. By reframing addiction as a systemic and transgenerational issue, this contribution supports psychotherapeutic approaches that prioritize relational change and family engagement in the treatment of addictive behaviors.